Low‐Temperature Sintered NTC Thermistor Ceramics for Thick‐Film Temperature Sensors. Issue 3 (21st February 2013) - Reimann, Timmy; Töpfer, Jörg; Barth, Stefan; Bartsch, Heike; Müller, Jens
<x xml:space="preserve">Abstract</x> Negative temperature coefficient (NTC) thermistor thick films were fabricated by screen printing on alumina substrates and firing at 900°C. Spinel‐type NiMn2O4 exhibits limited stability in air between 730 and 970°C only and interacts with the Bi2O3 additive. The Zn–Co‐substituted spinel Zn0.75Ni0.5Co0.5Mn1.25O4 with 3 wt% additive shows complete densification at 900°C; no interaction between spinel and additive was observed. Alternatively, a Cu–Zn–Co‐substituted Cu0.37Zn0.52Ni0.44Co0.44Mn1.23O4 spinel with excellent sintering characteristics even without sintering additive was investigated. The thermistor films display a sheet resistance of about 300 kΩ/□ and B = 3300 K. The firing behavior, microstructure formation, and electrical properties of NTC thick films are reported.